‘Dit is hoog tyd dat ons iets oor die tyd sê!’ – Nuwe Testamentiese perspektiewe op die Iaaste dae - Joubert, S. J. (Verbum et ecclesia, 1999)
"It is high time that we say something about time!" New Testament perspectives on the last days In this article Mediterranean views on time prevalent during the New Testament period, are discussed. The discussion is preceeded by an overview on apocalyptic thought in early Judaism(s), around the first two centuries BCE. The discussion on Mediterranean views on time is followed by an analysis of New Testament perspectives on the concept of time, as influenced by the impact of the Christ-event on early Christians’ understanding of the past, present and future. Various theological explanations for the delay of the "parousia" by New Testament authors, such as Paul and the authors of 2 Peter and Revelation, also receive attention.